Society's Acceptance of Children with Special Needs - Liza Angelina (State Institute of Islamic Studies Batusangkar, 2023)
The background of this research is the social acceptance of children with special needs, society's negative behaviors towards children with special needs (CWSN). Differences in characteristics among different societal groups arise due to variations in individuals' backgrounds within the community, such as education, professions, and so forth. This study is a qualitative research with a Literature Review approach. The focus of this research is to explore how society accepts the presence of children with special needs. The aim of this study is to gather information from the community regarding their opinions on children with special needs, both in general and specific contexts.